Pengaruh Lingkungan Kerja Non Fisik Terhadap Kinerja Pegawai Kelurahan Se-Kecamatan Rumbia Kabupaten Bombana - Muh. Fathir Maulid Yusuf, Ilham Akbar Garusu, Ahmad Hamid (LPPM Universitas Nahdlatul Ulama Sulawesi Tenggara, 2023)
Abstract This study aims to examine the influence of non-physical work environment on the performance of employees in the sub-district office of Rumbia, Bombana Regency. The data used in this research consist of quantitative and qualitative data, with the primary data source being raw data obtained directly from the research location, in the form of accountability reports, employee work target reports, questionnaires or surveys, and information gathered through interviews. The data were analyzed using simple linear regression analysis techniques to determine the relationship between the independent variables and the dependent variable in this study. The research results indicate that the non-physical work environment has a significant influence on employee performance, with a coefficient of 0.767 and a significance level of 0.001. This means that when the non-physical work environment, such as direct leadership, coworker relationships, and superior-subordinate relationships, improves, employee performance will also increase, thereby achieving the organizational performance targets, in this case, the sub-district office of Rumbia, Bombana Regency. Keywords: Non-Physical Work Environment, Employee Performance.